Gentlemen in Oppression : Exploring the Myth of Sex in Elliot Rodger's My Twisted World - Korhonen, Henna (My University, 2025)
The misogynistic subculture known as incels (involuntarily celibate), has gained notoriety for their extremely misogynistic belief system, in which women are the culprit for the incel’s virginity. While incels often reside on online platforms, this ideology has resulted in cases of real-life violence, the most notorious being the case of Elliot Rodger. Prior to murdering six people, himself, and injuring 14 on the Isla Vista college campus in 2014, Rodger released a personal manifesto titled My Twisted World, where his chauvinistic world view is unveiled. This thesis utilized Roland Barthes’ (1972) semiotic notion of myth in exploring how Rodger constructs the myth of sex in ‘My Twisted World’, or, sex as a second-order system. Defined by the connotative meanings added to the denotative, linguistic sign, myth proves a viable tool in uncovering the hidden meanings especially central in the construction of ideologies. The thesis aimed to identify how the myth of sex is constructed, and how the myth is naturalized via rhetoric tools. The results of the thesis showed that Rodger portrays the myth of sex as a tool of power used solely by women. In this, the connotations of competition and inequality were deemed prominent, stemming especially from the implied, animalistic and vicious nature of women To achieve this, the rhetoric tools of contrast, hyperbole, and metaphor were the most prominent in the manifesto. The results were in accordance with the already established, misogynistic incel ideology in which women are equated to animals posited as the enemy. Further this thesis emphasizes how misogynistic language can, at worst, lead to real-life mass-violence, if left unrecognized.
Keywords: incels, misogyny, hate speech, mass violence, ideology, myth, meaning, connotation, naturalization